2016
DOI: 10.1016/j.chroma.2016.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antioxidant activity in Victorian marine algal extracts using high performance thin-layer chromatography and multivariate analysis

Abstract: The aim of this study was to develop and validate a rapid and simple high performance thin layer chromatographic (HPTLC) method to screen for antioxidant activity in algal samples. 16 algal species were collected from local Victorian beaches. Fucoxanthin, one of the most abundant marine carotenoids was quantified directly from the HPTLC plates before derivatization, while derivatization either with 2,2-diphenyl-1-picrylhydrazyl (DPPH) or ferric chloride (FeCl) was used to analyze antioxidants in marine algae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 29 publications
2
10
0
1
Order By: Relevance
“…The best dose-response activity was observed for F. vesiculosus followed by C. baccata and H. elongata with a capacity of inhibiting 50% of DPPH (IC 50 ) at 7.17 ± 0.01 μg/mL ( F. vesiculosus ), 28.49 ± 3.80 μg/mL ( C. baccata ) and 64.89 ± 6.64 μg/mL ( H. elongata ). Our results concord with previous studies which describe green algae have lower free radical scavenging activities when compared to brown algae [ 25 , 26 , 27 ]. While high IC 50 values are found for pure or aqueous methanol extracts from Ulva species such as U. clathrata (715 μg/mL) [ 28 ], U. prolifera (3026 μg/mL) [ 28 ] and U. compresa (>1000 μg/mL) [ 26 ], low IC 50 values are observed in pure or aqueous methanol/ethanol extracts from Cystoseira species like C. sedoides (27 μg/mL) [ 29 ], C. baccata (28 μg/mL), C. usneoides (55 μg/mL) [ 26 ], C. osmundacea (69 μg/mL) [ 27 ] and C. tamariscifolia (109 μg/mL) [ 26 ].…”
Section: Resultssupporting
confidence: 92%
“…The best dose-response activity was observed for F. vesiculosus followed by C. baccata and H. elongata with a capacity of inhibiting 50% of DPPH (IC 50 ) at 7.17 ± 0.01 μg/mL ( F. vesiculosus ), 28.49 ± 3.80 μg/mL ( C. baccata ) and 64.89 ± 6.64 μg/mL ( H. elongata ). Our results concord with previous studies which describe green algae have lower free radical scavenging activities when compared to brown algae [ 25 , 26 , 27 ]. While high IC 50 values are found for pure or aqueous methanol extracts from Ulva species such as U. clathrata (715 μg/mL) [ 28 ], U. prolifera (3026 μg/mL) [ 28 ] and U. compresa (>1000 μg/mL) [ 26 ], low IC 50 values are observed in pure or aqueous methanol/ethanol extracts from Cystoseira species like C. sedoides (27 μg/mL) [ 29 ], C. baccata (28 μg/mL), C. usneoides (55 μg/mL) [ 26 ], C. osmundacea (69 μg/mL) [ 27 ] and C. tamariscifolia (109 μg/mL) [ 26 ].…”
Section: Resultssupporting
confidence: 92%
“…Fucoxanthin content. Fucoxanthin is main component of non-provitamin A carotenoid and has free radical scavenging activity due to unusual allenic double bonds (C=C=C) that is believed to be responsible for its higher antioxidant activity (Agatonovic-Kustrin et al, 2016). Fucoxanthin has been investigated as antitumor and cancer-preventative function that indicate inducing G1 cell-cycle arrest and apoptosis in various cell lines (Satomi, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported on the use of chemometric tools to classify plant foods. For example, principal component analysis (PCA) was used to outline of the similarities and differences among 16 algal species and to classify 40 wine samples based on their high-performance thin-layer chromatography (HPTLC) fingerprints [18,19]. It is well known that each plant species has a special, complex mixture of bioactive natural products, in which each component contributes to its overall bioactivity.…”
Section: Introductionmentioning
confidence: 99%